Effect of Addition of Silver Nanoparticle on Optical Properties of Polymethylacrelate (PMMA) Films - Adel H. Omran Alkhayatt (Journal of Global Pharma Technology, 2016)
The aim of this work to a realization the effect of adding silver nanoparticles on the optical properties of Polymethylmethacrylate (PMMA) films were prepared by using casting technique At a temperature (50ᵒC) with thickness (8±1μm).The optical properties by measuring the spectra absorbability and transmission as a function of wavelength (200-800) nm. The results showed that the transmittance decreased with increasing doping because of increased impurity resulted holds attenuation in the intensity of incident light with a clear increase of absorption and a decrease in optical reflectivity.as well as calculated the optical constants (α,k, and εr) of the prepared films and the results showed an increase when increasing rate of doping .the real part of the Dielectric Constant conduct like the refractive index, while the imaginary part conduct like the extinction coefficient, as for optical conductivity its values increases with increasing the rate of the silver nanoparticles as well as identifying the types of electronic transitions and calculating energy gaps It was found there is diminution in energy gap for direct electron transmission reaching values (5.4 - 4.9) eV.Keywords: Polymethylacrelate, Optical Properties, Silver Nanoparticle, Optical Conductivity